2010
DOI: 10.1186/1471-2458-10-60
|View full text |Cite
|
Sign up to set email alerts
|

Are we doing enough? Evaluation of the Polio Eradication Initiative in a district of Pakistan's Punjab province: a LQAS study

Abstract: BackgroundThe success of the Global Polio Eradication Initiative was remarkable, but four countries - Afghanistan, Pakistan, India and Nigeria - never interrupted polio transmission. Pakistan reportedly achieved all milestones except interrupting virus transmission. The aim of the study was to establish valid and reliable estimate for: routine oral polio vaccine (OPV) coverage, logistics management and the quality of monitoring systems in health facilities, NIDs OPV coverage, the quality of NIDs service delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 21 publications
5
38
0
Order By: Relevance
“…The study found, in agreement with previous studies [8,[13][14][15][16][17][18], that sociodemographic factors such as higher education, higher income, and having known other people (outside of one's own family) in the community who had TB were all associated with TB knowledge. It was also found that experiences with a TB patient, e.g., a close personal relationship with a patient with TB [18] was associated with better TB knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The study found, in agreement with previous studies [8,[13][14][15][16][17][18], that sociodemographic factors such as higher education, higher income, and having known other people (outside of one's own family) in the community who had TB were all associated with TB knowledge. It was also found that experiences with a TB patient, e.g., a close personal relationship with a patient with TB [18] was associated with better TB knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…The questionnaire included questions from WHO guidelines [22] and other literature reviews [8,15,16,23] on sociodemographic characteristics of the participants and their TB knowledge, attitudes, and practices [19]. The English questionnaire was translated by independent bilingual translators into the major target languages, Thai, Burmese, Khmer, and Lao, and was pre-tested in a sample of randomly chosen persons from the study area who did not form part of the main study.…”
Section: Measurementioning
confidence: 99%
See 2 more Smart Citations
“…All of the 20 lots were rejected for poor NIDs service delivery [28]. Similarly, in Baluchistan province, post-campaign monitoring results, showed repeated large numbers of missed children.…”
Section: Experts' Recommendationmentioning
confidence: 99%